IDS Bulletin - Institute of Development Studies (Brighton Institute of Development Studies, 1998)
IDS WP: The IDS Bulletin is an open access, peer-review journal exploring emerging international development challenges. It aims to contribute to critical thinking on how transformations that reduce inequalities, accelerate sustainability and build more inclusive and secure societies can be realised.
frequency changed c​urrent frequency 6 issues/year.
Keywords: Economic conditions; ECONOMIC CONDITIONS; ECONOMIC DEVELOPMENT; DEVELOPING COUNTRIES; PERIODICALS